2020
DOI: 10.1101/2020.09.30.317214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implantable photonic neural probes for light-sheet fluorescence brain imaging

Abstract: Significance: Light-sheet fluorescence microscopy is a powerful technique for high-speed volumetric functional imaging. However, in typical light-sheet microscopes, the illumination and collection optics impose significant constraints upon the imaging of non-transparent brain tissues. Here, we demonstrate that these constraints can be surmounted using a new class of implantable photonic neural probes. Aim: Mass manufacturable, silicon-based light-sheet photonic neural probes can generate planar patterned illu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The resonant collection of fluorescence with directional beamlets, whose angle depends on the spectral content, is an intriguing capability, which complements recent works that used diffractive elements to fabricate implantable probes for light‐sheet fluorescence imaging. [ 52 ] The plasmonic approach not only proves that this can be accomplished with a lossy material, but also allows using the zeroth order to impose or retrieve a spatial modulation, on the strength of the wavevector‐dependent momentum matching.…”
Section: Discussionmentioning
confidence: 99%
“…The resonant collection of fluorescence with directional beamlets, whose angle depends on the spectral content, is an intriguing capability, which complements recent works that used diffractive elements to fabricate implantable probes for light‐sheet fluorescence imaging. [ 52 ] The plasmonic approach not only proves that this can be accomplished with a lossy material, but also allows using the zeroth order to impose or retrieve a spatial modulation, on the strength of the wavevector‐dependent momentum matching.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a study performed by Sacher et al . [66] demonstrated that back grinding could be a suitable chip thinning method for photonic neural probes with a thickness ranging from 50–92 µm. In addition to this, there have been techniques explored to reduce mechanical damage to the chips caused by back grinding, such as the one explored by Morcom et al .…”
Section: Chip Thinning Methodsmentioning
confidence: 99%
“…On this topic, focused on the importance of nano-optics for targeted biosignals in tissues and real samples, the development of implantable photonic neural probes for light-sheet fluorescence brain imaging has recently been reported. 69 This imaging approach was successfully achieved by the use of a miniaturized optical setup along with the incorporation of a probe with a propagation capability of distances up to 300 μm in free space using fluorescent optical responsive beads suspended in agarose as medium. The different steps involved in the design and several lithography and surface modification techniques should also be mentioned.…”
Section: Current Trends and Future Perspectives Of Implantable Portab...mentioning
confidence: 99%